Etiologija in klinična slika duševne manjrazvitosti pri otrocih - Bon, Jurij (Medicinski razgledi, 1998)
Children with mental retardation constitute a group with special medical needs. There are several hundrede known etiological (mostly biomedical) factors, that can influence the development of a child's brain. We experience the changes in their prevalence rates, mainly because of improvements in health care. There is more than one etiological factor present in more than half of mentally retarded children. We are recognizing the role of psychosocial factors in development of borderline and mild mental retardation and the influence of personal characteristics, accompanying mental and somaticillnesses on the child's overall mental development. The objective today is to help children with individually adapted assistance, which enables them to remain in their domestic environment and improves their social skills.
Keywords: duševna zaostalost; Mental retardation; otroci; Diagnosis; Etiology; Child; Chromosome abnormalities; diagnostika